Case Report: Dermoscopic, High-Frequency Ultrasound, Contrast-Enhanced Ultrasound Appearances and Special Treatment of a Patient With Syringoid Eccrine Carcinoma on the Chest - Jing Zhang (Frontiers Media S.A., 2021)
This article aims to explain the use of a variety of noninvasive of minimally invasive examinations to obtain reliable diagnostic clues. The choice of treatment methods and repair techniques for wound defects are also critical in terms of the prognosis. Here, we describe the case of a 53-year-old male patient who visited our dermatology clinic due to a red plaque on the inner side of his left nipple without any symptoms for more than 30 years. He was given dermoscopy, high-frequency ultrasound (HFUS), Color Doppler flow imaging (CDFI), and contrast-enhanced ultrasound (CEUS) examinations. Currently, there are no literatures on these auxiliary examinations for this disease. Dermoscopy revealed that there were abundant blood vessels on the periphery of the skin lesion with obvious dilation. HFUS revealed an inhomegeneous hypoechoic solid mass in the dermis with clear borders and irregular shape. CDFI indicated that there are abundant blood flow signals in the periphery and central of the tumor. CEUS showed a mixed inhomogeneous, grid-like high-enhancement pattern. Based on the above auxiliary findings, the possibility of malignant lesion was suspected. Therefore, the patient was given a pathological examination, which showed that many luminal structures of the dermis layer were embedded in the hyperplastic fibrous tissue. The atypical cells were not obvious but showed an infiltrating growth pattern. Immunohistochemistry showed positive reaction for cytokeratin 7 (CK7), epithelial membrane antigen (EMA), and carcinoembryonic antigen (CEA) and a weak positive results was obtained for S-100. There was also a negative result for CK20, gross cystic disease fluid protein 15 (GCDFP-15), and P63. As a result, the patient was diagnosed with “syringoid eccrine carcinoma.” The treatment was surgical excision. Mohs microsurgery was combined with the looped, broad, and deep-buried suturing technique (LBD tension-reduced suturing technique). This technique directly sutures the wound instead of carrying out traditional skin grafting or flap transfer. The postoperative follow-up results were satisfactory as no obvious keloid formed on the wound during the follow-ups. In conclusion, ultrasound is greatly advantageous in tumor morphology and hemodynamics. It orients the therapeutic management and assesses the therapeutic efficacy and the tumoral prognosis. In surgical treatments, a less-traumatic operation should be selected to reduce the patient’s pain.